This preview shows page 1. Sign up to view the full content.
Unformatted text preview: s = ( p + p 2 ) 2 , t = ( k 2p 2 ) 2 , u = ( k 1p 2 ) 2 = u (see fgure below). Just like in class k 1 = ( E k 1 , v k 1 ), k 2 = ( E k 2 , v k 2 ), p = ( E p , v p ), and p 2 = ( E p 2 , v k 1 + v k 2v p ). k 1 k 2 p p 2 Show that d dt = r s ( s4 m 2 ) f ( s, t, u ) where u is now defned by u = 4 m 2st and s = ( k 1 + k 2 ) 2 still. (Hint: it is easier to prove this result by picking either the CMS Frame or the rest Frame oF one oF the initial state particles.) 1...
View
Full
Document
This note was uploaded on 07/28/2011 for the course PHYSICS 880.08 taught by Professor Staff during the Fall '10 term at Ohio State.
 Fall '10
 Staff
 Work, Quantum Field Theory

Click to edit the document details